Spiritual Emotional Freedom Technique untuk Mereduksi Psikosomatis Pada Ibu Rumah Tangga - Mahmuddah Dewi Edmawati; Hadi Warsito; Aldila Fitri RNM; Akhmad Setyawan (Universitas Islam Negeri Madura, 2024)
The purpose of this study was to find out whether the Spiritual Emotional Freedom Technique is effective in reducing psychosomatic symptoms in housewives. The research method used is experimental research. This type of research is a one group pretest-posttest design study. Sample data collection in this study used the purposive sampling method. Purposive sampling is a sampling technique with certain considerations. The reason for using this purposive sampling technique is because it is suitable for quantitative research, or studies that do not generalize. Data collection was obtained by filling in psychosomatic problem scale. The analysis used by researchers to determine the influence of each variable uses a non-parametric analysis test technique, namely the Wilcoxon Signed Rank Test. As for testing the hypothesis that reads Spiritual Emotional Freedom Technique is effective for reducing psychosomatic in housewives, based on the results in the table based on the results in the table obtained Z count of -2.023 with Asymp.sig (2-tailed) of 0.043. So it can be concluded that the Spiritual Emotional Freedom Technique is effective for reducing psychosomatic symptoms in housewives.